A new interleaved high step‐up soft switching converter with simple auxiliary circuit and reduced voltage stress. Issue 3 (17th October 2022) - Naeini, Omid Haghparast; Shaneh, Mahdi; Mohammadi, Mohammad Reza; Adib, Ehsan
Abstract: This paper proposes a soft‐switching high step‐up DC/DC interleaved boost converter. The converter uses an interleaved structure to decrease input current ripple. The coupled inductor technique achieves high voltage gain without needing the extremely increased duty cycle. The applied auxiliary circuit provides zero‐voltage‐switching (ZVS) condition for both main switches with a minimum number of elements. In addition, all the diodes turn off with zero‐current‐switching (ZCS), alleviating the reverse recovery problem. Moreover, all power switches and diodes have low voltage stress. The voltage stress of the auxiliary switch is low, resulting in low C oss losses of the auxiliary switch. The other properties of the proposed converters are continuous‐low‐ripple input current, no need for the floating gate drive, and small size. The theoretical analysis is validated by a 250‐W prototype with 40‐V input to 400‐V output voltage with a 100‐kHz.switching frequency.